Operacionalização para Portugal: critérios de Beers de medicamentos inapropriados nos doentes idosos. - Maria Augusta Soares; Fernando Fernandez-Llimós; Carmen Lança; José Cabrita; José A Morais (Acta Médica Portuguesa, 2008)
Elderly drug therapy needs special care considering physiopathological alterations of this age group that increase the risk of adverse drug events occurrence and due to the high number of drugs used. Several tools have been created, as tables of drugs and groups of drugs to be avoided in patients 65 years old and over. Beers Criteria of 2002 update is the most used tool.To operationalize Beers Criteria to be used by health care professionals in Portugal.Analysis of the drugs and therapeutic classes included into the Beers Criteria approved for market in Portugal and the identification of other approved substances included in the pharmacological classes mentioned in Beers Criteria. The two tables in the Beers criteria were adapted to substances approved in Portugal, even including other marketed active substances belonging to therapeutic classes mentioned in Beers criteria. Levels of inappropriateness and the potential effects after their use in elderly were also included. In Beers table 1, 34 included substances don't have approval in Portugal, and 4 have different denominations. In Beers table 2, three tricyclic antidepressants, 12 typical antipsychotics, 5 doses for short-action benzodiazepines, and 28 NSAIDs (being two coxibs) were included.The Portuguese operationalization of the Beers Criteria allows the creation of a tool that helps prescribers to choose drugs and doses for a safer prescription to the elderly. These adapted tables allow benchmarking among studies assessing inappropriateness of use of drugs in different countries using Beers Criteria.